In Vitro Functional Assessment of 22 Newly Identified CYP2D6 Allelic Variants in the Chinese Population - Dai, Da‐Peng; Geng, Pei‐Wu; Wang, Shuang‐Hu; Cai, Jie; Hu, Li‐Ming; Nie, Jing‐Jing; Hu, Ji‐Hong; Hu, Guo‐Xin; Cai, Jian‐Ping (Basic & clinical pharmacology & toxicology, 2015)
Cytochrome P450 2D6 (CYP2D6) is one of the most widely investigated CYPs related to genetic polymorphisms and is responsible for one‐quarter of the currently used clinical drugs. We previously detected 22 novel, non‐synonymous, mutated sites in the Chinese population, but nothing is known about the functional effects of these mutations in terms of specific CYP2D6 substrates. In this study, wild‐type CYP2D6, two common allelic variants and 22 newly reported CYP2D6 isoforms were transiently expressed in 293FT cells, and the enzymatic activities of these variants were systematically assessed using dextromethorphan and bufuralol as the probing substrates. Consequently, 19 and 21 allelic variants were found to exhibit significantly decreased enzymatic activities for dextromethorphan and bufuralol, respectively. Of 22 novel CYP2D6 variants, six allelic isoforms (CYP2D6.89, CYP2D6.92, CYP2D6.93, CYP2D6.96, E215K and R440C) exhibited absent or extremely reduced metabolic activities compared with those observed for the wild‐type enzyme. Our in vitro functional data can be useful for CYP2D6 phenotype prediction and provide valuable information for the study of clinical impact of these newly found CYP2D6 variants in China.